Review of the Stone Age Archaeology in Southwestern Angola - Matos, Daniela de (Africana Studia, 2020)
Africa has become a major focus on the debate of the emergence of modern human behavior and rise of anatomically modern humans due to increasing data on early Middle Stone Age sites in southern African territories. Southwestern Angola is one of the regions of great interest for the chronological framework of the Stone Age due to the geographic and geomorphological conditions similar to other southern African regions of the intertropical zone that allowed preservation of Middle and Late Pleistocene deposits with lithic materials. New methodological approaches have offered new insights on the ecodynamics of past human populations in Subsaharan Africa, attempting to understand their subsistence strategies along with landscape and resource management, their cognitive and adaptive evolution and their diachronic and synchronic cultural and technological features. However, despite the increasing knowledge on these issues, very little is known about the prehistory of the Portuguese speaking countries, such as Angola. Before the end of the dictatorship in Portugal and the independence of Angola as a Portuguese province in 1975, the National Board for Colonial Research (JIU) conducted a series of geographical, geological and anthropological missions. Between 1948 and 1955, the Geological Survey Brigade and the Anthropobiological Mission surveyed the Humpata Plateau and discovered a series of caves, rockshelters and open-air sites. A brief review of the historical background and current data on these collections is here presented based on the materials curated at the Tropical Research Institute (IICT) in Lisbon, Portugal. Key-words: Africa – Angola – Middle Stone age